(untitled) (Global Journal of Medical Research, 2013)
Understanding the definition and meaning of HIV/AIDS have implications not only for HIV/AIDS research, clinical practices but also the overall impact on mortality. The definitions of HIV/AIDS have changed in addition to the concepts and terminology associated with when talking about the history of HIV/AIDS. Previous study utilized World Health Organization (WHO)case definition of HIV/AIDS in predicting the relative effectiveness of HIV among individuals with tuberculosis (Kennedy, Campbell and Malinda, 2004).Their findings suggest that WHO case definitions significantly predicted HIV/AIDS among TBpositive HIV-positive participants compared to TB positive and HIV-negative participants(Kennedy, Campbell and Malinda 2004). Previous studies also indicate that WHO (1986) case definitions of HIV/AIDS, although well developed and assessed its uses were prevented by the proliferation of counseling and HIVtesting centers, particularly in the developing countries (Harries 1990; Lipson at al. 1995).